How do you find all the zeros of g(x) = x^5 – 8x^4 + 28x^3 – 56x^2 + 64x – 32 ?

1 Answer
Feb 28, 2016

Use the rational root theorem, polynomial division and completing the square to find roots:

x=2 (with multiplicity 3)

x=1+-sqrt(3)i

Explanation:

g(x)=x^5-8x^4+28x^3-56x^2+64x-32

By the rational root theorem, any rational zeros of g(x) must be expressible in the form p/q for integers p and q with p a divisor of the constant term 32 and q a divisor of the coefficient 1 of the leading term.

In addition note that g(-x) = -x^5-8x^4-28x^3-56x^2-64x-32 has no changes of sign in its coefficients, so there are no negative Real zeros.

Hence the only possible rational zeros are:

1, 2, 4, 8, 16, 32

We find:

g(2) = 32-128+224-224+128-32 = 0

So x=2 is a zero and (x-2) a factor:

x^5-8x^4+28x^3-56x^2+64x-32

=(x-2)(x^4-6x^3+16x^2-24x+16)

Let h(x) = x^4-6x^3+16x^2-24x+16

h(2) = 16-48+64-48+16 = 0

So x=2 is a zero of h(x) and (x-2) is a factor:

x^4-6x^3+16x^2-24x+16 = (x-2)(x^3-4x^2+8x-8)

Let k(x) = x^3-4x^2+8x-8

k(2) = 8-16+16-8 = 0

So x=2 is a zero of k(x) and (x-2) is a factor:

x^3-4x^2+8x-8 = (x-2)(x^2-2x+4)

The remaining quadratic factor can be factored by completing the square and using the difference of squares identity:

a^2-b^2 = (a-b)(a+b)

with a = x - 1 and b=sqrt(3)i

x^2-2x+4

= x^2-2x+1+3

= (x-1)^2-(sqrt(3)i)^2

= ((x-1)-sqrt(3)i)((x-1)+sqrt(3)i)

= (x-1-sqrt(3)i)(x-1+sqrt(3)i)

Hence the last two zeros are:

x = 1+-sqrt(3)i